Nonsurgical Treatment and Prevention of Osgood Schlatter Disease - Xu, Haoqian (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Teenagers are starting to participate in sports in greater numbers due to the recent expansion in the sports business and the spectacular holding of the Olympics in Paris. However, sports injuries during the sports process are also an unavoidable problem, such as tibial tuberosity osteochondritis (OSD), which is a high-incidence disease among adolescent athletes and is troubling many teenagers. The youth population represents the future of a country. Therefore, it is crucial to help them avoid OSD as much as possible and recover from it as soon as possible. This article briefly describes the diagnostic methods and risk factors of OSD, including clinical manifestations and analysis of the advantages and disadvantages of different diagnostic methods such as X-ray, ultrasound, and MRI. The focus is on non-surgical treatment and prevention of OSD, with a particular emphasis on physical therapy (including strength training (core stability training, and lower limb strength training), activity adjustment, stretching, and rehabilitation massage, as well as wearing orthopedic devices) and medication therapy.